Draft Annual Plan 1995-96 Government of Madhya Pradesh - Planning Commission (Planning Commission, 1995)
Though not economically developed, the work participation rate in the State is 42.82, which is much higher than the all India average of 37.46. The tribal districts have significantly higher female participation rate, bordering between 30 to more than 51 per cent. The population growth rate in the State during the decade 1981-91 was recorded as 26.84, as against only 23.85 for the country as a whole. The demographic scenario of the State is characterised by a very high birth rate (34.9), a significantly high death rate (12.9), as well as infant mortality rate (104).
Government of Madhya Pradesh, Planning, Economics and Statistics Department